PENGARUH PELATIHAN MENGGUNAKAN MODUL CARA MENYIKAT GIGI TERHADAP PENGETAHUAN GURU SD UNGGUL SAKTI KOTA JAMBI - Asio Asio (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2016)
TITLEThe influence of dental training with tooth brushing module to educational level of elementary school teachers in SD Unggul Sakti JambiABSTRACTElementary school health training is a main objective of health promotion. Society, which is the health promotion primary target must be empowered to accept and able to maintain and develop their own health. The increase of teacher’s participation and skill in health service is in accordance with authority delegation scope, that teachers are able to play active role in guiding their students in increasing dental and oral hygiene. The purpose of the research is to find out the impact of increasing the training using how to brush teeth module towards SD Unggul Sakti Kota Jambi teachers’ knowledge.It is a quasi experiment with pre-test and post-test control group design. The respondents are 18 Elementary school Unggul Sakti Jambi city teachers as control group and 18 Elementary School Sari Putra teachers as control group. For the knowledge variable, the data collection is by filling questionaire about elementary school teacher knowledge about brushing teeth before and after the training using brushing teeth module. The data analyzed with Wilcoxon test.Research result shows that p 0,001, which means that there is a significant differentiation of teacher’s knowledge between before and after the training. Median value (min-Max) 20 (19-20) (experiment group) and after the observation, the median value (Min-Max) 8.5 (7-14). So, it can be concluded that there is an impact of training using brushing teeth module towards SD Unggul Sakti Kota Jambi teacher’s knowledge. Keywords : elementary teacher training, knowledge, how to brush teeth